2017
DOI: 10.4236/jep.2017.82014
|View full text |Cite
|
Sign up to set email alerts
|

Growth Characteristics of <i>Fuirena umbellata</i> in a Surface Flow Constructed Wetland and Its Influence in Nutrients and Faecal Bacteria Removal from Domestic Wastewater in Cameroon

Abstract: Various configurations of vegetated bed systems with a variety of macrophytes have been tested experimentally in Cameroon, for the treatment of domestic wastewater. The aim of this work was to assess the growth and biomass production of Fuirena umbellata (Cyperaceae) and its potentials in the removal of faecal bacteria and nutrients from primarily treated domestic effluent. A wetland vegetated with this macrophyte and a non-vegetated wetland (control) were continuously fed with primarily treated domestic waste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 42 publications
3
9
1
Order By: Relevance
“…The growth parameters increased very slowly during the domestication phase as the plants were still struggling to adapt in their new but more polluted environment Wastewater is rich in nutrients that enrich and nourish the soil. Plants growing in wastewater constructed environment make use of these nutrients for their growth and development [15] [17]. The plants species in the CW showed increase in plants height and diameter has a function of the rich nitrate and phosphate habitat that the plants absorded for its metabolism.…”
Section: Shoot Production and Plants Densitymentioning
confidence: 99%
See 4 more Smart Citations
“…The growth parameters increased very slowly during the domestication phase as the plants were still struggling to adapt in their new but more polluted environment Wastewater is rich in nutrients that enrich and nourish the soil. Plants growing in wastewater constructed environment make use of these nutrients for their growth and development [15] [17]. The plants species in the CW showed increase in plants height and diameter has a function of the rich nitrate and phosphate habitat that the plants absorded for its metabolism.…”
Section: Shoot Production and Plants Densitymentioning
confidence: 99%
“…It is observed that more biodegradation of organic matter occurred in the wetland treatment beds such that the amount of phosphate in the outflow was more than the inflow especially in the treatment bed vegetated with Brilantaisia bauchiensis followed by the bed with Polygonum salicifolium. The high growth and the linear growth of these plants in the wastewater treatment station is probably due to the availability of nutrients particularly Nitrogen and phosphorus present in the water which probably resulted from the transformations of nitrates and phosphates since these compounds were abundantly available in the wastewater but were removed more in the vegetated beds than in the control [14] [15]. It is evident that the presence of wastewater significantly increased growth of shoots and plant density in CW [15] [32].…”
Section: Shoot Production and Plants Densitymentioning
confidence: 99%
See 3 more Smart Citations